Theorie und Empirie agrarstrukturellen Wandels?; Theory and Practice of Structural Change in Agriculture? - Stefan Mann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– The paper examines to which extent the theory of the farm household and the argument of path dependencies can be confirmed through recent empirical contributions on structural change in agriculture. In addition, a model is developed that explains structural change through occupational choices in favour or against farming. The validity of this model is challenged by empirical results, too. It can be shown that all three theoretical approaches contribute to explaining structural change in agriculture, which results to a coexistence of small and large farms if not hampered by political interference.
Keywords: 330; Agrarstruktur; Strukturwandel; Kleinbauern; Agrarökonomik